Moving, Making and Atmosphere: Routines of Home as Sites for Mundane Improvisation. (14th March 2016) - Pink, Sarah; Leder Mackley, Kerstin
Abstract: In this article, we examine how everyday atmospheres of home are made, maintained and improvised through habitual routines of movement, and the implications of this for co-design for energy demand reduction. Drawing on our ethnography of how people experienced and constituted a sensory aesthetic of home, we analyse the example of lighting use in night-time routines. We propose seeing these routines as sites of the possible, where everyday making might be engaged for co-design. Thus suggesting refocusing ethnographic design research beyond what people do in their homes, towards how they move through and make the atmospheres of their homes.